Distribution, sources and contamination assessment of heavy metals in surface sediments of the South Yellow Sea and northern part of the East China Sea. Issue 1 (15th November 2017) - Lu, Jian; Li, Anchun; Huang, Peng
Abstract: Surface sediment samples collected from the South Yellow Sea and northern part of the East China Sea during spring and autumn, respectively, were analyzed for grain size, aluminum, and heavy metals (Cr, Ni, Cu, Zn, and Pb) to evaluate heavy metal levels and the contamination status. The results showed that all of the heavy metal concentrations met the standard criteria of the Chinese National Standard Criteria for Marine Sediment Quality. Both the EFs and a multivariate analysis (PCA) indicated that Cr, Ni, Cu, and Zn were mainly from natural contributions, while Pb was influenced by anthropogenic inputs, especially during autumn. The geoaccumulation index of Pb near the mouth of the Yangtze River suggested that the pollution degree in autumn was heavier than that in spring, which might be caused by the greater river discharge in summer and more heavy metal adsorption with finer grain sizes. Highlights: Heavy metal concentrations of Cr, Ni, Cu, Zn, and Pb collected during different seasons were analyzed. Enrichment factors and PCA indicated that Pb was influenced by anthropogenic activities especially during autumn. The geoaccumulation index of Pb near the Yangtze River mouth suggested that the pollution degree was heavier in autumn.